Effect of Dietary Supplementation of Green Seaweed, Ulva Lactuca on Growth Performance, Digestive Enzymes and Histo-Architectural Changes of Labeo rohita (Hamilton, 1822) Fingerlings - A. P. Muralidhar; M. P. Singh Kohli; K. Pani Prasad; Karthireddy Syamala; A. K. Prusty (Journal of Indian Fisheries Association, 2021)
The eﬀect of dietary supplementation of green seaweed, Ulva lactuca on growth performance, digestive enzymes and histology of Labeo rohita fingerlings were studied for a period of 60 days. Two hundred and sixteen fingerlings (average weight 4.46 ± 0.04g) were randomly distributed into six treatment groups with three replicates each. Fishes were fed with six diﬀerent kinds of feeds namely, T-1 (Fish meal based control diet), T-2 (20g/kg Ulva in diet), T-3 (40 g/kg Ulva in diet), T-4 (80 g/kg Ulva in diet), T-5 (120 g/kg Ulva in diet) and T-6 (160 g/kg Ulva in diet). In the current experiment, parameters like weight gain%, SGR, FCR, FER, PER, ANPU and the body indices of the treatment groups fed with Ulva meal at diﬀerent inclusion levels were significantly diﬀerent (p<0.05) from the control group. However, U. lactuca inclusion greater than 4% had shown negative eﬀects. Among the digestive enzymes only amylase showed significant changes (p<0.05) due to seaweed inclusion. Protease and lipase have not shown any significant variation. Histological studies also supported the results obtained. In the present study dietary incorporation of U. lactuca at the rate of 40 g/kg hads shown a significant increase in the growth performance and feed utilization without causing any adverse eﬀects.